Implementasi Seven Tools Of Quality Di Industri Kecil Triple X Produksi Tas - Nizar Adlany; Said Salim Dahda; Moh. Jufriyanto (JATI EMAS (Jurnal Aplikasi Teknik dan Pengabdian Masyarakat), 2022)
Bags are accessories that are often used by students and workers to store their belongings. In Indonesia, there are many bag craftsmen and they have various qualities. Triple X SME is a small micro business and is classified as a bag production house industry. Maintaining quality consistency is a problem that occurs along the bag production line. Quality problems if not resolved will result in an increase in the cost of making the bag. Then the seven tools (7QC) one of the proven methods in dealing with this and as a result of the seven quality control instruments (7QC) reducing the number of manufacturing-related errors. These devices have proven to be quite useful in terms of increasing output and improving quality. As this case study can show, when 7QC techniques are used in a small business, they help deal with the problems experienced by the SME. During the first six months of the project, production lines are inspected, faults are categorized, and 7QC tools are implemented effectively and problems found exactly. As important as any tool in finding the root cause of a problem is, a cause and effect diagram is the most important.